The summer of good intentions - Francis, Wendy (Simon & Schuster Paperbacks, 2015)
"Three sisters and their families come together for their annual summer vacation on Cape Cod, where beloved traditions and long-held assumptions are jeopardized by the secrets each brings from home"--